2013
DOI: 10.1900/rds.2013.10.270
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-Rich Bilberry Ameliorates Total Cholesterol and LDL-Cholesterol when Implemented in the Diet of Zucker Diabetic Fatty Rats

Abstract: ■ AbstractBACKGROUND: Bilberries and blackcurrants are nutrient sources rich in bioactive components, including dietary fibers, polyphenols, and anthocyanins, which possess potent cardiovascular protective properties. Few studies investigating the cardio-protective effects of natural components have focused on whole bilberries or blackcurrants. OBJECTIVE: The aim of this trial was to investigate whether a diet enriched with bilberries or blackcurrants has beneficial effects on glucose metabolism, lipid profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 44 publications
2
37
0
1
Order By: Relevance
“…The results point to a possible heart protective effect of AMFJ, once it has in its composition phenolic compounds that might have antioxidant action, for example, the anthocyanins. Hypolipidemic and of oxidative stress effects were also shown in other studies [159, 160]. …”
Section: Introductionsupporting
confidence: 77%
“…The results point to a possible heart protective effect of AMFJ, once it has in its composition phenolic compounds that might have antioxidant action, for example, the anthocyanins. Hypolipidemic and of oxidative stress effects were also shown in other studies [159, 160]. …”
Section: Introductionsupporting
confidence: 77%
“…Cardiovascular diseases remain one of the leading causes of death and they are, therefore, a primary focus of research and treatment [75]. Several studies have shown that the intake of berry fruits was associated with a reduced risk of cardiovascular diseases.…”
Section: Cardioprotective Effectsmentioning
confidence: 99%
“…However, no effects on HDL cholesterol, glucose metabolism or blood pressure were observed. The authors concluded that the effect of bilberries on hypercholesterolemia could probably be attributed to their high anthocyanin content [94]. Likewise, in a study in alloxan-induced diabetic rats, supplementation with bilberry powder (2 g/day) for four weeks increased insulin and reduced total cholesterol, LDL cholesterol, VLDL cholesterol and TG levels, and prevented HDL cholesterol decline [95].…”
Section: Effect On Dyslipidemiamentioning
confidence: 98%